PENERAPAN MODEL PEMBELAJARAN PBL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS 3A SDN SARIREJO - Linda Pujianti; Veryliana Purnamasari; Riah Nurhayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to increase students' learning motivation by implementing the Problem Based Learning (PBL) learning model in class 3A science lessons at SDN Sarirejo. This type of research is classroom action research, carried out in 2 cycles where each cycle consists of 1 meeting consisting of 4 stages, namely: planning, action, observation and reflection. The data collection method uses questionnaires or questionnaires. The research subjects were 25 class 3A students at SDN Sarirejo. The general research results show an increase in the percentage of students' learning motivation in the pre-cycle, achieving results of 55.35% in the sufficient category, then in cycle 1 it increased to 67.54% in the high category, and in cycle 2 it increased to 84.55% with a very high category. This means that the application of the Problem Based Learning (PBL) learning model is able to increase students' learning motivation in class 3A science subjects at SDN Sarirejo.